A complexity reduction algorithm for depth maps intra prediction on the 3D-HEVC - Sanchez, Gustavo; Saldanha, Mario; Balota, Gabriel; Zatt, Bruno; Porto, Marcelo; Agostini, Luciano (2014 IEEE Visual Communications and Image Processing Conference, 2014)
This paper proposes a complexity reduction algorithm for the depth maps intra prediction of the emerging 3D High Efficiency Video Coding standard (3D-HEVC). The 3D-HEVC introduces a new set of specific tools for the depth map coding that includes four Depth Modeling Modes (DMM) and these new features have inserted extra effort on the intra prediction. This extra effort is undesired and contributes to increasing the power consumption, which is a huge problem especially for embedded-systems. For this reason, this paper proposes a complexity reduction algorithm for the DMM 1, called Gradient-Based Mode One Filter (GMOF). This algorithm applies a filter to the borders of the encoded block and determines the best positions to evaluate the DMM 1, reducing the computational effort of DMM 1 process. Experimental analysis showed that GMOF is capable to achieve, in average, a complexity reduction of 9.8% on depth maps prediction, when evaluating under Common Test Conditions (CTC), with minor impacts on the quality of the synthesized views.